Laryngopharyngeal Reflux Disease in North of Jordan, Prevalence, Awareness and Risk Factors - Allan, Hadeel; Kanaan, Yazan; Al Omari, Ahmad (Jordan Medical Journal, 2025)
Background: laryngopharyngeal reflux (LPR) is the result of retrograde flow of gastric contents to the laryngopharynx, where it comes in contact with tissues of the upper aero-digestive tract. Aims: We aimed to determine the prevalence and awareness of laryngopharyngeal reflux (LPR) in general population of North Jordan, along with identifying associated risk factors. Methodology: A cross-sectional study was carried out to determine the prevalence of laryngopharyngeal reflux (LPR) by utilizing the Reflux Symptoms Index (RSI) questionnaire among a randomly chosen group of adult participants. Those scoring ≥13 on the RSI were identified as laryngopharyngeal reflux (LPR) patients, while those scoring <13 were classified as non- laryngopharyngeal reflux (LPR) subjects. The questionnaire was completed by a total of 500 participants, comprising 275 males and 225 females. Results: The prevalence of LPR in the North Jordanian population was determined to be 28%, with no statistically significant difference observed between genders (p > 0.05). Notably, the age group above 40 years exhibited a higher prevalence rate. Tobacco smoking emerged as the most significant factor associated with LPR. Remarkably, only 1% of participants demonstrated awareness of LPR and its relationship with throat or voice symptoms. Conclusion: laryngopharyngeal reflux (LPR) was found to be prevalent in 28% of the North Jordanian population, with a strikingly low level of awareness (1%). The study identified tobacco smoking as a prominent risk factor for laryngopharyngeal reflux (LPR). Furthermore, individuals who reported consuming higher amounts of caffeinated beverages displayed a greater incidence of laryngopharyngeal reflux (LPR). However, the study did not examine the relationship between alcohol consumption and LPR due to the absence of alcohol-drinking participants in the sample.